2022
DOI: 10.1007/s12325-022-02074-9
|View full text |Cite
|
Sign up to set email alerts
|

Managing Cachexia in Head and Neck Cancer: a Systematic Scoping Review

Abstract: Introduction: Patients with head and neck cancer (HNC) are usually confronted with functional changes due to the malignancy itself or its treatment. These factors typically affect important structures involved in speech, breathing, chewing, swallowing, and saliva production. Consequently, the intake of food will be limited, which further contributes to loss of body weight and muscle mass, anorexia, malnutrition, fatigue, and anemia. This multifactorial condition can ultimately lead to cancer cachexia syndrome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
0
22
0
1
Order By: Relevance
“…Patients who are identified as being malnourished with loss of FFM might be considered for active physical therapy and nutritional consultation early on, before cachexia is established. 60,61 Among the strengths of this prospective cohort study are the considerable size of the cohort and the prospective nature of data collection. In addition, the information gathered on patient body weight 6 months prior to diagnosis adds further depth to our data and has only been reported in a few previous studies on HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who are identified as being malnourished with loss of FFM might be considered for active physical therapy and nutritional consultation early on, before cachexia is established. 60,61 Among the strengths of this prospective cohort study are the considerable size of the cohort and the prospective nature of data collection. In addition, the information gathered on patient body weight 6 months prior to diagnosis adds further depth to our data and has only been reported in a few previous studies on HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In order words, the use of repeated BIA measurements could be a tool to guide the development of a personalized approach in the nutritional treatment of patients with HNSCC. Patients who are identified as being malnourished with loss of FFM might be considered for active physical therapy and nutritional consultation early on, before cachexia is established 60,61 …”
Section: Discussionmentioning
confidence: 99%
“…A recent publication has reported that higher energy intake is necessary for cachexic patients treated for head and neck cancer to maintain skeletal muscle mass. 120 However, another study found KD to be more effective than insulin in reversing weight loss, reducing tumor size, and promoting weight gain. 121 We recommend further research on this matter.…”
Section: Adverse Effects Contraindications and Issues Of Concern When...mentioning
confidence: 99%
“…Multiple barriers to adoption exist, including the reliance on small, single-institution datasets, the lack of external validation and generalizability, insufficient transparency and reproducibility of ML research, and no clear superior predictive modeling strategies [109–110,111 ▪ ]. Significant variations exist in data collection methods and data is not open-access, which limit the combination of various sources of data for robust model training using large datasets [112].…”
Section: Important Limitations In Current Applications Of Machine Lea...mentioning
confidence: 99%
“…It is therefore important to include diversity and socioeconomic metrics in ML algorithms in HNC clinical sciences to ensure generalizability, improve accuracy, and reduce bias. A regulatory framework for data collection, model development, performance metrics, external validation, and reporting is necessary to facilitate the recommendation of models for clinical evaluation [112,118]. Risk of bias assessment tools can be applied to evaluate data quality [111 ▪ ].…”
Section: Important Limitations In Current Applications Of Machine Lea...mentioning
confidence: 99%